From Monopoly to Machine-opoly: Rethinking Market Regulations for Autonomous AI Agents - Anna Maria Tri Anggraini; Ahmad Sabirin; Jimi Rambo Arranchado (Universitas Negeri Semarang, 2026)
The paper examines the effectiveness and relevance of business competition law in regulating market dynamics in the AI era, and formulates an adaptive regulatory framework that aligns technological developments with the principles of justice and accountability. The method used is a normative-legal-research method with a qualitative approach. The paper's findings are that in the digital era driven by AI, the paradigm of business competition is undergoing a fundamental transformation that demands a profound reflection on existing legal principles. The phenomenon of machine-opoly, monopolies generated by autonomous AI agents, challenges traditional concepts of fair competition. This issue underscores the tension between technological innovation as a force for value creation and the need for fairness and balance in the market. From a theoretical perspective, AI presents non-human actors running complex algorithms, which opens up space for collusion and market domination practices that are difficult to detect and control by conventional regulation. The emergence of machine-opoly transformed traditional monopolies into dominance based on algorithms, data, and autonomous artificial intelligence. Through the TFEU and AI Act, the EU has integrated transparency and accountability into competition law, followed by the US, the UK, Australia, and China with similar adaptive measures. Indonesia, through Law No. 5 of 1999, still faces limitations in regulating algorithmic behavior. Therefore, regulatory reforms that emphasize algorithmic transparency and supervisory capacity are essential to maintain the fairness and innovation of digital markets.